2022
DOI: 10.1155/2022/6836966
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Curative Effect and Prognostic Factors of Anterior Cervical Surgery for Spinal Cord Injury without Radiographic Abnormalities

Abstract: Objective. The study aimed to investigate the effect of anterior cervical surgery in the treatment of spinal cord injury without radiographic abnormalities (SCIWORAs) and analyze the related factors affecting the prognosis of patients. Methods. A total of 86 patients with SCIWORA who were admitted to our hospital from June 2018 to March 2021 were selected as the research subjects. According to the different treatment methods selected by the patients, they were divided into the control group (n = 38) and the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The presence of comorbid conditions, such as dementia/delirium and post-injury pneumonia, can hinder the prospects of rehabilitation, leading to poorer neurological improvement. Other studies have suggested that younger age, cervical myelopathy at baseline, spinal cord compression ratio, and time from injury to treatment are independent prognostic factors [73][74][75]. Previous studies have demonstrated that physical examinations are a reliable method for predicting neurological improvement in patients with non-surgically treated C3-4 CSCI without major bone injury.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…The presence of comorbid conditions, such as dementia/delirium and post-injury pneumonia, can hinder the prospects of rehabilitation, leading to poorer neurological improvement. Other studies have suggested that younger age, cervical myelopathy at baseline, spinal cord compression ratio, and time from injury to treatment are independent prognostic factors [73][74][75]. Previous studies have demonstrated that physical examinations are a reliable method for predicting neurological improvement in patients with non-surgically treated C3-4 CSCI without major bone injury.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%